A meta-frontier assessment of bank efficiency in Middle East and North Africa countries. Issue 2 (13th February 2017) - Abid, Ihsen; Goaied, Mohamed
Abstract : Purpose: The purpose of this paper is to evaluate and compare the efficiency ratios and the technological gaps of banking industries in seven countries of the Middle East and North Africa (MENA) region. Design/methodology/approach: The meta-frontier model was used to evaluate efficiency across countries that may have different production technologies. Findings: The results of the meta-frontier analysis of banking systems over the period from 1991 to 2011 showed that Tunisian banks were the most efficient in terms of cost and profit. For the cost (profit) model, the analysis of the technological gap showed that Egyptian (Tunisian) banks used the most advanced technology in offering financial services to clients. The comparison of efficiencies confirmed that most efficient banks in terms of cost are not necessarily the most efficient in terms of profit and vice versa. The authors also concluded that cost efficiency analysis provides a partial view of banking efficiency and hence, profit efficiency analysis is as important. Originality/value: The study is relevant for policymakers, regulators and monetary authorities and for researchers to know more about the real differences of efficiency of banks across countries in MENA region and to clarify the sources of this inefficiency to better adapt to the new environment, to make strategic decisions and to reference the performance of banking institutions.